Determining the Pore Size Distribution in Synthetic and Building Materials Using 1D NMR - Nagel, Sarah Mandy; Strangfeld, Christoph; Kruschwitz, Sabine (Diffusion Fundamentals, 2019)
NMR is gaining increasing interest in civil engineering for applications regarding microstructure characterization as e.g., to determine pore sizes or to monitor moisture transport in porous materials. This study reveals the capability of NMR as a tool for pore size characterization. Therefore, we measured floor screed and synthetic materials at partial and full saturation. For most examined materials, the pore size distribution was successfully determined using either a reference or a calibration method. Since diffusion effects were observed for some samples in single-sided NMR measurements, further tests employing an NMR core analyzer were carried out in a homogeneous magnetic field. The finally obtained surface relaxivity of floor screed (50 μm/s) resulted to be much higher than suggested by literature.